High Histone Deacetylase 2/3 Expression in Non-Functioning Pituitary Tumors - Zhao, Wenxiu; Jiang, Xiaobin; Weisenthal, Karrin; Ma, Jun; Botticelli, Erin M.; Zhou, Yunli; Hedley-Whyte, E. Tessa; Wang, Baiyao; Swearingen, Brooke; Soberman, Roy J.; Klibanski, Anne; Zhang, Xun (Frontiers in Oncology, 2022)
Epigenetic modification of chromatin is involved in non-malignant pituitary neoplasia by causing abnormal expression of tumor suppressors and oncogenes. These changes are potentially reversible, suggesting the possibility of targeting tumor cells by restoring the expression of epigenetically silenced tumor suppressors. The role of the histone deacetylase (HDAC) family in pituitary tumorigenesis is not known. We report that HDAC2 and 3, Class I HDAC members, are highly expressed in clinically non-functioning pituitary adenomas (NFPAs) compared to normal pituitary (NP) samples as determined by RT-PCR and immunohistochemical staining (IHC). Treatment of a human NFPA derived folliculostellate cell line, PDFS, with the HDAC3 inhibitor RGFP966 for 96 hours resulted in inhibition of cell proliferation by 70%. Furthermore, the combination of RGFP966 with a methyltransferase/DNMT inhibitor, 5’-aza-2’-deoxycytidine, led to the restoration of the expression of several tumor suppressor genes, including STAT1, P16, PTEN, and the large non-coding RNA tumor suppressor MEG3, in PDFS cells. Our data support the hypothesis that both histone modification and DNA methylation are involved in the pathogenesis of human NFPAs and suggest that targeting HDACs and DNA methylation can be incorporated into future therapies.